Constructing Equity Investment Strategies Using Analyst Reports and Regime Switching Models - Taguchi, Rei; Watanabe, Hikaru; Sakaji, Hiroki; Izumi, Kiyoshi; Hiramatsu, Kenji (Frontiers in Artificial Intelligence, 2022)
In this study, we demonstrate whether analysts' sentiments toward individual stocks are useful for stock investment strategies. This is achieved by using natural language processing to create polarity index from textual information in analyst reports. In this study, we performed time series forecasting for the created polarity index using deep learning, and clustered the forecasted values by volatility using a regime switching model. In addition, we constructed a portfolio from stock data and rebalanced it at each change point of the regime. As a result, the investment strategy proposed in this study outperforms the benchmark portfolio in terms of returns. This suggests that the polarity index is useful for constructing stock investment strategies.